2005
DOI: 10.1007/s00125-005-1812-5
|View full text |Cite
|
Sign up to set email alerts
|

Increased augmentation of central blood pressure is associated with increases in carotid intima–media thickness in type 2 diabetic patients

Abstract: Aims/hypothesis: Type 2 diabetes is associated with a two-to seven-fold increase in cardiovascular morbidity and mortality. The aim of this study was to determine the relationships between intima-media thickness (IMT), an established marker of atherosclerosis, large artery function and other determinants of cardiovascular risk in type 2 diabetic patients. Methods: We studied 228 type 2 diabetic patients (75 women, aged 62±2 years [mean± SEM]). Carotid IMT was bilaterally measured using ultrasound technology. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
2
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 64 publications
2
19
2
3
Order By: Relevance
“…This is in accordance with findings by Westerbacka et al, [20] which also showed that increased augmentation pressure correlated with duration of diabetes.…”
Section: Non-invasive Markers Of Atherosclerosissupporting
confidence: 93%
“…This is in accordance with findings by Westerbacka et al, [20] which also showed that increased augmentation pressure correlated with duration of diabetes.…”
Section: Non-invasive Markers Of Atherosclerosissupporting
confidence: 93%
“…[28][29][30][31][32][33] Furthermore, several studies have reported that alteration of arterial stiffness occur in subjects with impaired glucose tolerance, polycystic ovaries, and newly diagnosed type 2 diabetes. [34][35][36] Moreover, in our study, we found a correlation between PWVft and insulinresistance state of GDM women, as assessed by the level of HOMA-IR index. In other words, pregnancies complicated by insulin resistance are independently associated with enhancement of maternal arterial stiffness.…”
Section: Discussionsupporting
confidence: 70%
“…4 There is now established evidence that aortic stiffness increases with aging and prolonged elevation of blood pressure, 5 and is the underlying pathology of isolated systolic hypertension. 6 Aortic stiffness is closely associated with cerebral large-arterial disease involving the extracranial internal carotid [7][8][9] and intracranial large arteries. 10 It is not possible to study the direct association of aortic stiffness with changes in cerebral microvessels, which cannot be routinely assessed with current imaging technology.…”
Section: Introductionmentioning
confidence: 99%